THE MODEL OF PATIENT SATISFACTION AND TRUST: A STUDY AT BPJS PATIENT - Peni Cahyati (Dinasti Publisher, 2021)
Health is a major requirement for every resident living in this world, and health development essentially concerns both physical and mental health. The state of health of a person will be influential on the aspects of social life is economic, and the continuity of the life of a nation and a country anywhere in the world, both in countries that have developed and in developing countries such as Indonesia as well as health is a right and an investment for all citizens of Indonesia. The research method uses descriptive analysis and verification analysis. By using a combination of analytical methods can be obtained by generalizing that is comprehensive. Samples taken as many as 100 patients BPJS health center Purbaratu Tasikmalaya City and sampling was done randomly or random sampling. Data analysis used is SEM (Stucture Equation Model). Based on the results of the research can be known that there are degrees of contribution of the variable provision of a service to trust patients through the patient satisfaction. The better the delivery of services provided by the health center Purbaratu Tasikmalaya City the better satisfaction of the patients received that will ultimately have an impact on the increased confidence of the patient to the health center Purbaratu the City of Tasikmalaya.